Development of Submerged ARC Welding Fluxes for Welding of API 5L X65 Steels - Singh, Gurpreet (My University, 2012)
The present work is an attempt to study the effect of flux on the tensile strength, Impact strength,micro hardness, and microstructure of high strength low alloy steel welds made by the submerged arc welding. The parent metal, heat affected zone and weld metal regions of each weldment have been examined. The effect of different kind of fluxes by keeping the welding parameters like welding current, welding voltage and welding speed constant has been evaluated for the different high strength low alloy weld joints. The microstructure evolution in these weld joints has also been studied and attempt has been made to correlate the observation. Further it has also been found out the best suited fluxes for welding of pressure vessel steels as per requirement. Mechanical and fracture properties of the steel have also been investigated.
M.E. (CAD/CAM and Robotics)
Keywords: Submerged Arc Welding; Welding Fluxes; Pressure Vessels; Micro Hardness